Effect of nutrition education integrating the health belief model and theory of planned behavior during pregnancy on gestational weight gain and birth weight in Southeast Ethiopia using complex analyses - Girma Beressa; Susan J. Whiting; Tefera Belachew (BMC Pregnancy and Childbirth, 2025)
Abstract Background The incidence of inadequate or excessive gestational weight gain (GWG) is an indicator of reproductive health problems. However, scientific evidence for the effect of nutrition education during pregnancy on GWG and neonatal birth weight (BW) in urban settings in Ethiopia is sparse. This study aimed to assess the effect of nutrition education during pregnancy on GWG and neonatal birth weight (BW) in urban settings in Southeast Ethiopia. Methods A community-based two-arm parallel cluster randomized controlled trial was conducted among 447 randomly selected pregnant women attending antenatal care (224 intervention and 223 control) from February to December 2021. Study participants were selected by multistage cluster sampling followed by systematic sampling. Women receiving the intervention received six nutrition education sessions, while women in the control group received standard care. GWG was the difference between the last recorded weight before delivery and the weight recorded during the first trimester. BW was measured within the first hour of delivery. The generalized structural equations model (GSEM) and structural equations model (SEM) were used to examine the direct, indirect, and total effects of nutrition education on GWG and BW via the dietary diversity score (DDS), food security (FS), and knowledge. Results The GSEM revealed that receiving intervention during pregnancy had a total effect on GWG [(AOR = 2.056, 95% CI: 1.705, 2.695)]. Having dietary diversity had direct and total effects on GWG [(AOR = 1.105, 95% CI: 1.022, 1.196)]. Having food security had a total effect on GWG [(AOR = 1.928, 95% CI: 1.817, 2.052)]. Having fruit and vegetable knowledge had a total effect on GWG [(AOR = 1.971, 95% CI: 1.856, 2.105)]. The SEM revealed that receiving intervention during pregnancy had a direct effect on BW (unstandardized β = 0.144, 95% CI: 0.034, 0.252). Similarly, it revealed that receiving intervention during pregnancy had a direct effect on DDS (β = 0.580, 95% CI: 0.024, 1.038). Likewise, it indicated that receiving intervention during pregnancy had a total effect on increasing BW (β = 0.137, 95% CI: 0.029, 0.243). Nevertheless, there was no statistically observed indirect effect of nutrition education during pregnancy on GWG and BW via mediators. Conclusion The SEM revealed that receiving nutrition education interventions during pregnancy had a total effect on GWG and direct and total effects on BW. The generalized structural equation modelling (GSEM) and structural equation modelling (SEM) findings show that integrating theory-based nutrition education during pregnancy will improve gestational weight gain (GWG) and birth weight (BW) in Ethiopia. Trial registration The trial was registered on Pan African Clinical Trials Registry (PACTR202201731802989, retrospectively registered on 24/01/ 2022).